Educational Attainment of Children Born with Unilateral Cleft Lip and Palate in the United Kingdom. (May 2021) - Grewal, Sukhraj S.; Ponduri, Sirisha; Leary, Sam D.; Wren, Yvonne; Thompson, John M. D.; Ireland, Anthony J.; Ness, Andy R.; Sandy, Jonathan R.
Objective: This study evaluated association between functional outcomes in children born with unilateral cleft lip and palate (UCLP) and educational attainment. Design: Cleft Care UK (CCUK) was a United Kingdom (UK) wide cross-sectional study. Setting: UK Cleft Teams (data collected from all UK sites providing centralized cleft services). Patients, Participants: Five-year olds born with nonsyndromic UCLP (n = 268). Main Outcome Measure(s): National tests for educational attainment Key Stage 1 (KS1) undertaken by children at age 7 were linked to CCUK data to describe differences in educational attainment. Associations between functional outcomes and KS1 results were evaluated using regression analysis. We adjusted for birth month, gender, and an area-based measure of socioeconomic status. Results: Data were available for 205 children with UCLP. These children scored lower than national average (NA) scores across all subject areas, with a 0.62 lower score observed in the Average Point Score (APS; P = .01). There was association between being in a lower category for a cleft related outcomes and poorer KS1 results, with a trend for poorer attainment with higher numbers of poor functional outcomes. Those with 3 or more poor outcomes had a −2.26 (−3.55 to −0.97) lower APS compared to those with 0 to 1 poor outcomes. Conclusions: Children born with UCLP have poorer educational attainment at age 7 across all subject areas though differences were modest. Children with poor functional outcomes at age 5 had worse educational outcomes age 7. Improvements in functional outcomes could enhance educational outcomes.